ENCOURAGING STUDENTS TO IMPROVE SPEAKING SKILLS THROUGH COMMUNITY LANGUAGE LEARNING - Kurnia, Kurnia (Study Program of English Literature, 2019)
Particularly for speaking skill, the students often find some problems. The problem frequently found is that their native language causes they difficult to use the foreign language. Other reason is because lack of motivation to practice the foreign language in daily conversation. English teacher should be able to motivate the learners in learning this foreign language. Motivation is a change of energy in a person's which is characterized by the emergence of affective and reaction to achieve the goals. It should be done by every English teacher in order that the students are interested to learn this language. English teacher must be able to manage the teaching by using certain method in the teaching-learning process, so that the students will like it without boring and despair. This research focused to find out whether community language learning method able to overcome the problem. It is proved by the difference between pre-test and post-test result of the three components speaking ability and final score of the students speaking ability